Pedagogical Skills Needs of Motor Vehicle Mechanics Work Teachers for Effective Content Delivery in Government Science and Technical Colleges in Adamawa and Taraba States - Kumazhege, Stephen Z.; Obadiah, Yusuf Andy; Aliyu, Yelwa (Lembaga Yasin AlSys, 2024)
The main purpose of the study was to explore the pedagogical skills needs of motor vehicle mechanics work teachers for effective content delivery in government science and technical colleges in Adamawa and Taraba States. The study was guided by two research questions and two null hypotheses. The study was conducted in Adamawa and Taraba States using descriptive survey research design. The population of the study was 123 respondents comprising 81 MVMW teachers and 42 instructors from all the 21 BEST Centres and Government Science and Technical colleges in Adamawa and Taraba States, Nigeria. There was no sampling as the entire population was used because it was manageable. A structured questionnaire tagged: Pedagogical Skills Needs of Motor Vehicle Mechanics Works Teachers Questionnaire (PSNMVMWTQ) consisting of 30 items was validated by three experts. The Instrument was trial tested in Gombe State and the Cronbach Alpha reliability method was used to test the reliability of the instrument and a 0.84 reliability coefficient was obtained. Data collected for the study was analyzed using Statistical Package for Social Sciences (SPSS) version 27.0. Mean statistics was used to answer the two research questions while a t-test was used to test the null hypotheses at a 0.05 level of significance. The findings of the study revealed among others that pedagogical skills needed include stimulating critical thinking, designing effective evaluation procedures, and implementing appropriate instruction. Similarly, affective skills were deemed needed including effective communication, active listening, and conflict resolution. Importantly, there were no significant differences between instructors and MVMW teachers regarding the perceived importance of these skills. It is recommended that Given the identified pedagogical skills needs of motor vehicle mechanics work (MVMW) teachers, Ministries of Education should design and implement targeted training programs focusing on instructional goal identification, task analysis, instructional design, questioning techniques, and evaluation procedures.